2013
DOI: 10.1159/000360034
|View full text |Cite
|
Sign up to set email alerts
|

UK Renal Registry 16th Annual Report: Chapter 15 Epidemiology of Reported Infections amongst Patients Receiving Dialysis for Established Renal Failure in England from May 2011 to April 2012: a Joint Report from Public Health England and the UK Renal Registry

Abstract: Introduction: Infection remains one of the leading causes of mortality in established renal failure patients receiving renal replacement therapy (RRT). Since 2007, centres providing RRT in England have been asked to provide additional data on patients with methicillin resistant Staphylococcus aureus (MRSA) bacteraemia. Since 2011, the option to provide data on methicillin sensitive Stapylococcus aureus (MSSA) and Escherichia coli bacteraemia, as well as Clostridium difficile infection has also been available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This report has presented data from one year of infections in ERF patients receiving dialysis and extends the work done in previous reports from Public Health England and the UK Renal Registry [2]. Numbers and rates of MRSA BSIs in dialysis patients have fallen in each of the last six years this report has been published.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This report has presented data from one year of infections in ERF patients receiving dialysis and extends the work done in previous reports from Public Health England and the UK Renal Registry [2]. Numbers and rates of MRSA BSIs in dialysis patients have fallen in each of the last six years this report has been published.…”
Section: Discussionsupporting
confidence: 60%
“…The previous report confirmed that whilst dialysis patients remained at increased risk from MRSA there has been a continued year on year decline in the number of reported episodes of bacteraemia [2].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…39 Furthermore, among chronic dialysis patients, asymptomatic carriers of resistant bacteria are prevalent. [40][41][42] A curative approach to AML may be futile among patients in whom the predicted survival due to their kidney disease is short even prior to the development of leukemia. 43,44 Realistic expectations and the desired goals of therapy must be discussed between the patient, family, nephrologist, and hematologist.…”
mentioning
confidence: 99%
“…Numbers of PDR Gram-negative infections expected in each of these groups were estimated for each year subsequent to the scenario. Projected estimates of the annual number of patients were made using HES [26] for all groups apart from renal dialysis, which used data from the UK Renal Registry [27]. The incidences of Gram-negative infections for large bowel surgery, hip replacement surgery, and repair of fractured neck of femur were obtained from mandatory and voluntary surgical site infection (SSI) surveillance [28].…”
Section: Methodsmentioning
confidence: 99%